Supervision of medical activities - Strban, Grega (Medicine, Law & Society, 2016)
It is investigated what kind of supervision could be exercised over medical activities in order to ensure the highest attainable quality of healthcare and access to medical services. To this end rights and especially duties of healthcare providers, definitions of sickness and effective healthcare provision, as well as various supervisory mechanisms and procedures for enforcing the rights, are analysed. It is argued that legal definitions of sickness and effective healthcare provision, stricter supervisory mechanisms and a single, legally regulated professional complaint procedure are required de lege ferenda.
Keywords: healthcare provision; sickness; mandatory health insurance; supervision; complaint proceedings; judicial review